Global vs. group-specific business cycles: The importance of defining the groups - Tino Berger; Marcus Wortmann (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
The literature on international business cycles has employed dynamic factor models to disentangle global from group-specific and national factors in countries' macroeconomic aggregates. Therefore, the countries have simply been classified ex ante as belonging to the same region or the same level of development. This paper estimates a DFM for a sample of 106 countries and three variables (output, consumption, investment) over the period 1960 to 2014, in which the countries are classified according to the outcome of a cluster analysis. By comparing the results with those obtained by the previous grouping approaches, we show substantial deviations in the importance of global and group-specific factors. Remarkably, when the groups are defined properly, the 'global business cycle' accounts for only a very small fraction of macroeconomic fluctuations, most evidently in the industrialized world. The group-specific factors, on the other hand, play a much greater role for national business cycles than previously thought - also in the pre-globalization period.
Keywords: C32; C38; E32; F44; 330; international business cycles; globalization; regionalization; dynamic factormodels; cluster analysis